SNHG11: A New Budding Star in Tumors and Inflammatory Diseases - Wu, Yinxin (Mini Reviews in Medicinal Chemistry, 2023)
Background: Long non-coding RNAs (lncRNAs) are transcripts that are over 200 nucleotides in length and lack protein-coding potential. Despite their name, lncRNAs have important regulatory roles in transcription, translation, and protein function by interacting with DNA, RNA, and protein molecules. Small nucleolar RNAs (snoRNAs), found in various tumors, are encoded by lncRNAs and have gained attention in recent research. The lncRNAs, encoding snoRNAs are known as small nucleolar RNA host genes (SNHGs), a newly identified class of lncRNAs. SNHG11, a specific SNHG, is a critical regulatory factor involved in various biological processes. Accumulating evidence suggests that SNHG11 can impact tumor development and inflammatory diseases by modulating downstream gene expression through chromatin modification, transcription, or post-transcriptional mechanisms. The expression levels of SNHG11 vary significantly in different normal tissues, tumors, and stages of tumor development. Currently, treatment options for advanced cancers are mainly palliative and lack curative potential. Objectives: This review aims to explore the modifications and functions of lncRNA SNHG11 in various tumors and inflammatory diseases. Through a comprehensive analysis of relevant literature on SNHG11 in PubMed, the review aims to provide a comprehensive description of the roles of SNHG11 in known tumors and inflammatory diseases and elucidate the specific mechanism’s underlying functions. The changes in SNHG11 expression in tumors and inflammatory diseases can serve as early biomarkers, therapeutic targets, and prognostic indicators. Improving the clinical detection, staging, treatment, and prognosis of tumors is of great value. Additionally, the structural modifications of SNHG11 can potentially enhance its function as a drug carrier to maximize the therapeutic potential of drugs. Furthermore, understanding the specific mechanisms of SNHG11 in tumors and inflammatory diseases may provide new ways for targeted therapy. Materials and Methods: Relevant studies were retrieved and collected from the PubMed system. SNHG11 was identified as the research object, and research literature on SNHG11 in the past ten years was analyzed to determine its strong association with the onset and progression of various diseases. The precise mechanisms of SNHG11's mode of action were reviewed, and references were further determined based on their impact factors for comprehensive analysis. Results: Through review and analysis, it was found that SNHG11 is involved in a wide range of tumors and inflammatory diseases through its high expression, including lung cancer, colorectal cancer, prostate cancer, hepatocellular carcinoma, triple-negative breast cancer, gastric cancer, glioma, ovarian cancer, pancreatic cancer, acute pancreatitis, and ischemic stroke, but with lower expression in virus myocarditis. SNHG11 is abnormally expressed in cells of these tumors and inflammatory diseases mainly contributes to disease proliferation, metastasis, ceRNA activity, miRNA sponging, drug resistance, and tumor prognosis. However, the specific mechanisms of SNHG11 in tumors and inflammatory diseases require further detailed exploration. Understanding the known regulatory mechanisms can expand the scope of clinical applications and promote early clinical detection, monitoring, and treatment. Conclusion: LncRNA SNHG11 can serve as an early diagnostic biomarker, therapeutic target, and prognostic indicator in various diseases, particularly tumors. SNHG11 plays a crucial role in the occurrence and development of tumors and inflammatory diseases through various mechanisms, which has significant implications for clinical diagnosis and treatment.
Keywords: LncRNA